Lista anotada de los termites en Cuba - Cruz, H.=700 1 Triguero, N.; Lopez, R.; Berrios, M. del C.; Varela, Y.; Fernandez, A.; Betancourt, M.; Sosa, C.; Valle, M.
(Es, En)
Ilus., 13 ref.
Keywords: TERMITIDAE; ISOPTERA; DISTRIBUCION GEOGRAFICA; HUESPEDES; COLECCIONES; CUBA; TERMITAS